Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

solve by using substitution
-7x-2y=-13   and   x-2y=11


Sagot :

luana
[tex] \left \{ {{-7x-2y=-13} \atop {x-2y=11}} \right. \\\\ \left \{ {{-7x-2y=-13} \atop {x=11+2y}} \right.\\\\ Substitute\ second\ equation\ into\ the\ first\ one:\\\\ -7(11+2y)-2y=-13\\ -77-14y-2y=-13\\ -77-16y=-13\ \ \ |Add\ 77\\ -16y= 64\ \ \ |Divide\ by\ -16\\ y=-4\\\\x=11+2y=11+2*(-4)=11-8=3\\\\ \left \{ {{y=-4} \atop {x=3}} \right. [/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.